Financial burden and health-seeking behaviors related to chronic diseases under the National Health Insurance Scheme in Bolikhamxay Province, Lao PDR: a cross-sectional study - Tomoo Ito; Sengchanh Kounnavong; Chiaki Miyoshi (BMC, 2022)
Abstract Background Chronic diseases pose a serious threat to health and longevity worldwide. As chronic diseases require long periods of treatment and may become serious conditions, the ensuing financial burden is often worse than that for non-chronic diseases. In 2016, the Lao PDR implemented the National Health Insurance (NHI) system, which covers select provinces. However, data on health service accessibility and the financial burden on households, especially those with chronically ill members covered by the NHI, are scarce. Methods This study used a cross-sectional design. Data collection was conducted in Bolikhamxay province (population = 273,691), from January 15 to February 13, 2019. In total, 487 households, selected through stratified random sampling, were surveyed via questionnaire-based interviews. Healthcare service usage and financial burden were examined. Results A total of 370 households had at least one member with self-reported health issues within the last 3 months prior to the interview, while 170 had at least one member with a chronic condition. More than 75% of the households accessed a health facility when a member experienced health problems. The majority of households (43.2%) spent the maximum value covered by the NHI, but households in the second largest group (21.4%) spent 10 times the maximum value covered by the NHI. The prevalence of catastrophic health expenditure (i.e., health-related expenditure equivalent to > 20% of total income) was 25.9% (20% threshold) and 16.2% (40% threshold). Through logistic regression, we found that the major factors determining financial catastrophes owing to health problems were household members with chronic illness, hospitalization, household poverty status, household size (for both the 20 and 40% thresholds), visiting a private facility (20% threshold), and distance from the province to the referral hospital (40% threshold). Conclusions The NHI system has had a positive effect on households' access to health facilities. However, catastrophic health expenditure remains high, especially among chronically ill patients. Facilities under the NHI system should be improved to provide more services, including care for chronic conditions.